Mechanical properties and water absorption behaviour of recycled cellulose fibre reinforced epoxy composites - Alamri, Hatem; Low, It Meng (Elsevier Ltd, 2012)
Recycled cellulose fibre (RCF) reinforced epoxy composites were fabricated with fibre loadings of 19, 28, 40 and 46 wt%. Results showed that flexural strength, flexural modulus, fracture toughness and impact strength increased as the fibre content increased. The ultimate mechanical properties were achieved with a fibre content of 46 wt%. The effect of water absorption on mechanical and physical properties of RCF/epoxy composites was investigated. The values of maximum water uptake and diffusion coefficient were found to increase with an increase in fibre content. Flexural strength, modulus and fracture toughness decreased as a result of moisture absorption. However, the impact strength was found to increase slightly after water absorption. XRD, FTIR and SEM studies were carried out to evaluate the composition and microstructure of RCF and RCF/epoxy composites.